PBL-Based E-LKPD Using Quizizz to Improve Students' Problem-Solving Abilities - Mardiati; Erika Sabila; Sri Zulhayana (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2026)
The low involvement and independence of students due to the use of conventional LKPD, which is less engaging, and the minimal integration of technology make it difficult for students to solve contextual problems. This study aims to analyze validity, assess practicality, and test the effectiveness of PBL-based E-LKPD assisted by Quizizz to improve students' problem-solving abilities. The method used is Research and Development, using the ADDIE model, and involves eighth-grade students at Khadijah Junior High School. Data collection methods use tests, questionnaires, and interviews. Data were collected through validity, practicality, and effectiveness tests, which were analyzed descriptively. The results show that the validity aspect obtained an average of 88% from material experts and 89.33% from design experts, both of which are categorized as "very valid". The practicality aspect reached 92.38% (individual test), 91.78% (small group), and 90.34% (large group), all of which are categorized as "very practical". Effectiveness based on the average N-Gain score of 0.83 (high category), stating that this media is effective in improving problem-solving abilities. Thus, the Quizizz-assisted PBL-based E-LKPD is a valid, practical, and effective mathematics learning innovation. This research implies that the Quizizz-assisted PBL-based ELKPD developed can help students understand the material well and also improve their problem-solving skills.